Pancreaticopleural Fistula: A Review of Imaging Diagnosis and Early Endoscopic Intervention. (19th August 2018) - Kord Valeshabad, Ali; Acostamadiedo, Jennifer; Xiao, Lekui; Mar, Winnie; Xie, Karen L.
Abstract : A 49-year-old male with history of chronic alcohol-induced pancreatitis presented with one month of worsening left pleuritic chest pain and shortness of breath. Chest radiograph demonstrated bilateral pleural effusions. Thoracentesis revealed increased amylase in the pleural fluid. Computed tomography (CT) and magnetic resonance cholangiopancreatography (MRCP) showed a fistula tract between the left pleural cavity and pancreas which was confirmed on endoscopic retrograde cholangiopancreatography (ERCP). Patient was treated with placement of a pancreatic stent with complete resolution of the fistula tract approximately in 9 weeks. A systematic literature search was performed on reported cases with pancreaticopleural fistula (PPF) who underwent early therapeutic endoscopy within the last 10 years. Imaging modalities, particularly CT and MRCP, play essential role in prompt preprocedural diagnosis of PPF. Early therapeutic ERCP is an effective and relatively safe treatment option for PPF, so invasive surgery may be avoided.